The modern existence of folklore of the Gayninsky Bashkirs of the Bardymsky district of the Perm Krai - Abdullina, Gulfira R.; Alimbaeva, Gul'shayan G.; Sultanova, Zilya A. (The New Research of Tuva, 2024)
The article presents an analysis of the current state of folkloric genres among the Gayninsky Bashkirs in the Bardymsky district of the Perm Krai. The authors based their research on materials from an expedition to the region in 2023 and compared them with the results of previous expeditions conducted by scientists in 1963, 2006 and 2013 to assess the degree of preservation of local folkloric material.During the analysis, it was discovered that large epic works had ceased to be used in everyday life by the beginning of the current century. The only surviving epic legend about the ancestors of the Gainin people, the brothers Aina and Gaina, has been recorded. According to experts, this is part of an ancient Bashkir epic that has previously been recorded and included in scholarly collections, as mentioned in the available scientific literature.Folklore songs, which also dominated the last century, are characterized by the disappearance of the genres of long-drawn-out songs of the Ozon Koy and Baits. Currently, only short songs and chants are recorded. Religious chants, known as Munajats, are widely used in the current Gainin culture. The most common genres of folklore are small ones, such as proverbs, sayings, omens and benevolence.
Keywords: Bashkirs; Gaininsky Bashkirs; Bashkir folklore; epic genre; takmak; Munazhat; preservation of folklore